EFEKTIFITAS KOMBINASI LATIHAN OTOT PROGRESIF DAN RELAKSASI AUTOGENIK TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI - Ayu Norita Putri; Gamya Tri Utami; Sri " Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Hypertension is a heart and blood vessel disease that signed with increased of blood pressure. A person get hypertension if blood pressure higher than 140/90 mmHg. The combination progressive muscle exercises and autogenic relaxation is one of non- pharmacological hypertension management. This research aim to find the effectivity of combination of progressive muscle exercises and autogenic relaxation to blood pressure of patients with hypertension. The research used quasy experiment design with non equivalent control group. This research conducted in Puskesmas Harapan Raya 30 hypertension samples, which divided into 2 group, 15 as experiment group and 15 as control group. The samples chosen with purposive sampling technique. Experimental group given combination progressive muscle exercises and autogenic relaxation for 30 minutes in every session for three days, meanwhile control group were not. The blood pressure was measured with digital sphygmomanometer and observation sheet. The analysis using univariate to identifying the frequencies and bivarite using independent t test and mann whitney. The result of this research showed that difference of mean sistolic and diastolic in experiment group and control group of first day, second days, and third days with p value 0,919, 0,161, 0,048) (<0,05) (systole) dan p value (0,011, 0,037, 0,026) (<0,05)  (dyastole). This research showing that combination of progressive muscle exercises and autogenic relaxation are effective for reducing blood pressure of hypertension. The result becomed recommanded to be applied for nursing interventation to reducing blood pressure of hypertension patients.Keywords: Autogenic relaxation, blood pressure, hypertension, progressive muscle exercises